Activity syndromes and metabolism in giant deep-sea isopods. (March 2017) - Wilson, Alexander D.M.; Szekeres, Petra; Violich, Mackellar; Gutowsky, Lee F.G.; Eliason, Erika J.; Cooke, Steven J.
Abstract: Despite growing interest, the behavioural ecology of deep-sea organisms is largely unknown. Much of this scarcity in knowledge can be attributed to deepwater animals being secretive or comparatively 'rare', as well as technical difficulties associated with accessing such remote habitats. Here we tested whether two species of giant marine isopod ( Bathynomus giganteus, Booralana tricarinata ) captured from 653 to 875 m in the Caribbean Sea near Eleuthera, The Bahamas, exhibited an activity behavioural syndrome across two environmental contexts (presence/absence of food stimulus) and further whether this syndrome carried over consistently between sexes. We also measured routine metabolic rate and oxygen consumption in response to a food stimulus in B. giganteus to assess whether these variables are related to individual differences in personality. We found that both species show an activity syndrome across environmental contexts, but the underlying mechanistic basis of this syndrome, particularly in B. giganteus, is unclear. Contrary to our initial predictions, neither B. giganteus nor B. tricarinata showed any differences between mean expression of behavioural traits between sexes. Both sexes of B. tricarinata showed strong evidence of an activity syndrome underlying movement and foraging ecology, whereas only male B. giganteus showed evidence of an activity syndrome. Generally, individuals that were more active and bolder, in a standard open arena test were also more active when a food stimulus was present. Interestingly, individual differences in metabolism were not related to individual differences in behaviour based on present data. Our study provides the first measurements of behavioural syndromes and metabolism in giant deep-sea isopods. Highlights: We measured individual consistency in activity & metabolism in two species of marine isopod. Both species show an activity syndrome across environmental contexts (presence/absence of food stimulus). Trends in behavioural/metabolic traits differed between sexes & species. Individual differences in metabolism were not related to individual differences in behaviour. Study represents first measurements of personality/ behavioural syndromes in a deep-sea organism.